Delay Analysis in Zigbee Wireless Communication for Manipulated Data and Finger Clip Sensor Data Using Xbee Pro S2C - Musayyanah; Pauladie Susanto; Weny Indah Kusumawati (Fakultas Teknik Universitas Bhayangkara, 2017)
Wireless Personal Area Networks have battery powered, low data rate, and low cost, that have been researched invarious fields, like Xbee Pro S2C. It can build mesh network, consist of Coordinator, Router and End Device. Xbeecan perform point to point and multipoint communication. We evaluate delay performance and data loss for bothcommunication at indoor environment, to get Xbee’s successful transmission rate. This transmission sent themanipulated data and data from sensor finger clip by End Device Node as Tranmitter to Coordinator Node asReceiver. This data is sent with different interval time, 8ms for manipulated data and 500 ms for data finger clipsensor. Definition of Delay is the difference of difference of time between first data sent and first data received.From manipulated data measurement the delay of point to point is 1,17 seconds, whereas multipoint gets 1,332seconds. For delay data finger clip measurement of multipoint is 1,34 seconds. While data loss occur in multipointcommunication, for data finger clip measurement get the loss 53,33 % and 46,67% in random quartile of data, andfor manipulated data get 3,56 % loss.